Guillotiner les simples d’esprit et les « demi-fous » ? Atténuation de la responsabilité pénale et application de la peine de mort (France, IVe République) - Nicolas Picard (Criminocorpus)
The Chaumié circular introduced the notion of « diminished responsibility » in 1905 in order to consider criminal defendants with mental retardations or psychic abnormalities. During the Fourth Republic (1947-1959), psychiatric examinations were almost always conducted in criminal cases, especially when the death penalty was at stake. It was then assumed that the mentally unbalanced and retarded criminals shouldn't be executed. However, a study of the pardon requests indicates that a « diminished responsibility » could not always prevent an execution. The president of the Republic had the right to pardon these criminals but it seems that the conclusions of psychiatric examinations influenced the decisions only to a limited extent.